Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

simplify the expression and combine like terms. 4 (z - 2) + 2 (z - 1)

Sagot :

4 (z - 2) + 2 (z -1)
(4)^(z)+(4)(-2)+(2)^(z)
= 4z+-8+2z+-2
= -4z+-8+2z+-2
=(4z+2z)+(-8+-2)
= 6z+-10